Software compensation for execution time delay in hybrid computation - Alford, Cecil O. (Computers & electrical engineering, 1975)
A hybrid computer is a highly interactive design tool for complex physical problems. Typically, problem design follows very much the same procedure one uses when the design tool is an all digital computer. The major problems are somewhat different however. The principle difference lies in the fact that a hybrid computer solves the design equations effectively using a first order numerical method. This leads to some rather serious error considerations which have been pointed out by various authors and are restated in this paper for completeness. Of these errors one of the more serious is that due to the evaluation of functions of the digital computer, referred to as execution time delay. The reduction or elimination of this error is the subject of this paper. Two primary methods for the reduction or elimination of execution time delay have been considered; function sequencing, and function extrapolation techniques. A Taylor series approach is given which eliminates execution time delay in certain cases, at the expense of additional computational complexity. An extrapolation method, based on the Lagrangian interpolation formula is described which reduces execution time delay errors and is computationally appealing.